2015
DOI: 10.1080/14780887.2015.1106630
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the possibility for secondary traumatic stress among transcriptionists: a grounded theory approach

Abstract: While there is a small, growing literature that considers the psychological safety of researchers, little attention has been paid in the qualitative literature to the wellbeing of transcriptionists. Transcriptionists play an integral and essential role in qualitative research but are often overlooked in terms of the emotional impact of the work. In the article we have interviewed transcriptionists and, using grounded theory, we illustrated that that they experienced emotional distress and feelings of helplessn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The authors recommended the introduction of a research team approach as an additional safeguard for transcriptionists; a similar recommendation has been made with regard to professional interpreters (Lai & Costello, 2020). In particular, they felt that they should be briefed about any potentially distressing content to the recordings that they are transcribing, as this would provide an opportunity to make an informed decision regarding taking on the role and prepare them for any potential emotional impact (Kiyimba & O’Reilly, 2016a). MacLean et al (2004) also highlight the impacts of emotionally laden content on transcriptionists, on a personal level and on the quality of transcripts produced; they advocate that necessary protocols are put in place, including briefing and debriefing.…”
Section: Why It Is Important To Consider the Psychological/emotional ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recommended the introduction of a research team approach as an additional safeguard for transcriptionists; a similar recommendation has been made with regard to professional interpreters (Lai & Costello, 2020). In particular, they felt that they should be briefed about any potentially distressing content to the recordings that they are transcribing, as this would provide an opportunity to make an informed decision regarding taking on the role and prepare them for any potential emotional impact (Kiyimba & O’Reilly, 2016a). MacLean et al (2004) also highlight the impacts of emotionally laden content on transcriptionists, on a personal level and on the quality of transcripts produced; they advocate that necessary protocols are put in place, including briefing and debriefing.…”
Section: Why It Is Important To Consider the Psychological/emotional ...mentioning
confidence: 99%
“…Twenty years ago, guidelines for the safety of social researchers were issued by the Social Research Association (2001) . Little attention, however, has been paid to the psychological safety of transcriptionists ( Kiyimba & O’Reilly, 2016a , 2016b ), who can potentially experience secondary stress and vicarious trauma ( Kiyimba & O’Reilly, 2016b ) which may be similar to the experiences of professional interpreters ( Geiling et al, 2021 ; Lai & Costello, 2020 ). Transcriptionists may also work on different projects, successively or in parallel, which may be of a similar nature, with the potential for long-term impacts.…”
Section: Why It Is Important To Consider the Psychological/emotional ...mentioning
confidence: 99%
“…Exposures to secondary trauma and various forms of violence is a familiar but underappreciated burden that many research assistants across the world (Powell & Lloyd, 2001; Shannonhouse, Barden, Jones, Gonzalez, & Murphy, 2016), particularly in low‐resource contexts, face when gathering data for population health research (Ng et al, 2016). Even evidence of secondary trauma among transcriptionists is known (Kiyimba & O'Reilly, 2016). Before we launched the COVID‐19 and mental health study, we developed an informal emotional debriefing program to provide basic psychoeducation and mental health resources for my research staff given the heavy nature of our data collection.…”
Section: Strategies For Promoting Mental Health In Community and Resementioning
confidence: 99%
“…Studies of specific research roles have found that among transcriptionists (transcribing qualitative interviews), exposure to sensitive health information and descriptions of difficult experiences such as end-of-life issues, child abuse, and mental health were identified as specific topic areas contributing to traumatic stress (Kiyimba & O'Reilly, 2016; Wilkes, Cummings, & Haigh, 2014). Specifically, transcriptionists in these studies endorsed experiencing a number of symptoms including negative emotions (e.g., anger, sadness, exhaustion) and physical distress (e.g., nausea, headaches).…”
Section: Mental Health Distress Among Researchersmentioning
confidence: 99%